Benchmarking of Intangible Assets in the Shipping Industry - Zhykharieva, Vlada (Transactions on Maritime Science, 2025)
The purpose of the paper is to develop a methodical approach to benchmarking of intangible assets on the example of the shipping industry in the context of the influence of intangibles on the financial results and market capitalisation of companies. The methodology of the research is based on a systematic approach, theory of benchmarking, financial analysis and assets valuation, theoretical foundations of maritime economics, and finance. The following scientific methods were used in the study: analysis and synthesis of results and retrospective, methods of econometrics, comparative, logic, and analytical methods. A methodical approach to comparative analysis of financial indicators, characterising intangible assets and their interpretation, has been elaborated. The proposed approach is illustrated on the example of container companies. The approach to benchmarking intangibles in the shipping industry makes it possible to perform a statistical analysis of indicators characterising the impact of the value of intangible assets on the financial results of shipping and logistics companies and their market capitalisation. The shipping industry is characterised by a low share of intangible assets, however, the growth in the share of intangibles has shown their importance for improving business efficiency of shipping companies in terms of financial indicators. The growth dynamics of goodwill to assets ratio has demonstrated the intensification of merger and acquisition processes in container sector of liner shipping. The multiples of financial results to the value of intangible assets were supplemented by correlation-regression analysis of dependence of the net profit on the value of intangibles. Analysis of the share of intangible assets in the market capitalisation and Tobin’s Q make it possible to assess the impact of the value of intangibles on the market value of companies. The results of analysis of annual Tobin’s Q showed the assets of container companies to be slightly undervalued by capital markets.